Ah, Sweet Mystery of Life : The Country Stories of Roald Dabl - Dahl, Roald; Illustrated by Lawrence, John (London Penguin Books, 2011)
Whether it is taking a troublesome cow to be mated with a prime bull; dealing with a rat-infested hayrick; learning the ways and means of maggot farming; or describing the fine art of poaching pheasants using nothing but raisins and sleeping pills, the author brings his stories of everyday country folk and their strange passions to life.
Include Picture
Keywords: Great Britain -- Short stories -- Country life